Review of the existing maximum residue levels for cypermethrins according to Article 12 of Regulation (EC) No 396/2005. (16th March 2023) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Binaglia, Marco; Brancato, Alba; Cabrera, Luis Carrasco; Castellan, Irene; Castoldi, Anna Federica; Chiusolo, Arianna; Crivellente, Federica; Del Aguila, Monica; Ferreira, Lucien; et al.
Abstract: According to Article 12 of Regulation (EC) No 396/2005, EFSA has reviewed the maximum residue levels (MRLs) currently established at European level for the group of pesticide active substances cypermethrins. To assess the occurrence of cypermethrin, alpha‐cypermethrin, zeta‐cypermethrin, beta‐cypermethrin residues in plants, processed commodities, rotational crops and livestock, EFSA considered the conclusions derived in the framework of Regulation (EC) No 1107/2009, the MRLs established by the Codex Alimentarius Commission (codex maximum residue limits; CXLs) for cypermethrin, alpha‐cypermethrin and zeta‐cypermethrin as well as the European authorisations and import tolerances reported by Member States and the UK (including the supporting residues data) for cypermethrin and zeta‐cypermethrin . The toxicological profile of zeta‐cypermethrin was also assessed. Based on the assessment of the available data, MRL proposals were derived, and a consumer risk assessment was carried out. Some information required by the regulatory framework was missing and a possible chronic/acute risk to consumer was identified. Hence, the consumer risk assessment is considered indicative only, all MRL proposals derived by EFSA still require further consideration by risk managers and measures for reduction of the consumer exposure should also be considered.